Effects of 6-week sprint-strength and agility training on body composition, cardiovascular, and physiological parameters of male field hockey players - Sharma, H. B.; Kailashiya, J. (The Journal of Strength and Conditioning Research, 2018)
Optimal physiological and cardiovascular characteristics are essential for optimal physical performance. Different types of training regimes affect these characteristics and lead to trainees' adaptation and changes in relevant parameters. In the present interventional study, we have evaluated the effects of 6-week sprint-strength and agility training on such parameters. Twenty-four young Indian national hockey players volunteered for this study. Body weight (BW), body mass index (BMI), percentage body fat, lean body mass (LBM), resting heart rate (rHR), resting blood pressure (rBP), resting double-product (rDP), P/power (using Running-based Anaerobic Sprint Test), vertical jump (VJ), seated shot put test (SP), ball-hitting speed (BS), Tm (505-agility test), and VO2max were measured, and changes (d) after specified training regime were studied. The training proved to be "short yet effective." Significant improvements after training were found in body composition, cardiovascular, aerobic, anaerobic, strength, agility, and performance-related parameters; but not in BW, BMI, P/LBM, SP/LBM, and VO2max/LBM. Change in VJ (dVJ) was associated with change in Tm (dTm); change in SP (dSP) with change in VO2max, which also related to change in rHR, rBP and rDP. Change in BS (dBS) was more among those with lower initial BW, BMI, and BF. dBS, along with change in VO2max/LBM, was more mainly among those with lower initial anaerobic-aerobic fitness. The findings will be useful for coaches, sports managers, players, and also for general population for better, individual, and sport-based designing of "short yet effective" training programs and monitoring of outcomes. Specific physiological parameter improvement-targeted training can also be designed based on this research.